Antibody Responses Elicited by Immunization with BG505 Trimer Immune Complexes - Gach, Johannes S. (J Virol, 2019)
Immune complex (IC) vaccines have been successfully used to increase immune responses against various pathogens, including HIV-1. Additionally, IC vaccines can induce qualitatively different antibody responses, with distinct antigenic specificities compared to the same antigens used alone. Here we measured the HIV-1-specific antibody responses in female New Zealand White rabbits after immunization with ICs made from BG505 SOSIP.664 trimers (BG505 trimers) and three rabbit monoclonal antibodies (MAbs) with different neutralization profiles. Two of the MAbs were specific for a hole in the glycan shield of the BG505 trimer, while the third, which bound less avidly, was specific for determinants at the gp41-gp120 interface. We found that immunization with one of the glycan-hole-specific ICs resulted in lower levels of trimer-binding antibodies compared to vaccination with the uncomplexed trimer, and that ICs made using either of the glycan-hole-specific MAbs resulted in lower rates of anti-trimer antibody decay. We concluded that ICs based on MAbs that bound to the immunodominant glycan hole epitope likely diverted antibody responses, to some extent, away from this site and to other regions of the trimer. However, this outcome was not accompanied by a widening of the breadth or an increase in the potency of neutralizing antibody responses compared with uncomplexed trimers. IMPORTANCE Immunodominant epitopes may suppress immune responses to more desirable determinants, such as those that elicit potentially protective neutralizing antibody responses. To overcome this problem, we attempted to mask immunodominant glycan holes by immunizing rabbits with ICs consisting of the BG505 SOSIP.664 gp140 trimer and MAbs that targeted the glycan holes. We found that IC vaccination likely diverted antibody responses, to some extent, away from the glycan holes and toward other regions of the trimer. IC vaccination resulted in slower decay of HIV-1-specific antibodies than did immunization with uncomplexed trimer. We did not observe a widening of the breadth or an increase in the potency of neutralizing antibody responses compared to uncomplexed trimers. Our results suggest that selective epitope dampening of BG505 trimers by ICs is rather ineffective. However, IC vaccination may represent a novel means of increasing the duration of vaccine-induced antibody responses.